2022
DOI: 10.3390/ijerph192417079
|View full text |Cite
|
Sign up to set email alerts
|

Association between Physical Activity Levels and Brain Volumes in Adults Visiting Radio-Imaging Center of Tertiary Care Hospital

Abstract: Background and aim: There is evidence to support the favorable impact of physical activity (PA) on brain volume. However, the empirical evidence exploring the relationship between physical and sedentary behavior remains mixed. We aimed to explore the relationship between physical activity and sedentary behavior and brain volume. Methods: The study sample (n = 150, mean age= 39.7 years) included patients interviewed with the International Physical Activity Questionnaire (IPAQ) who underwent an MRI brain scan. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…The potential mechanisms linking sedentary behavior with cognitive function are poorly understood. Previous studies have suggested that less sedentary time (or more physical activity) is associated with fewer brain lesions such as brain atrophy and white matter hyperintensities (WMHs) [15,16]. In addition, the extent of brain atrophy and WMHs has been associated with accelerated cognitive impairment and dementia in middle-aged and older adults [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The potential mechanisms linking sedentary behavior with cognitive function are poorly understood. Previous studies have suggested that less sedentary time (or more physical activity) is associated with fewer brain lesions such as brain atrophy and white matter hyperintensities (WMHs) [15,16]. In addition, the extent of brain atrophy and WMHs has been associated with accelerated cognitive impairment and dementia in middle-aged and older adults [17,18].…”
Section: Introductionmentioning
confidence: 99%